2014
DOI: 10.3989/redc.2014.3.1130
|View full text |Cite
|
Sign up to set email alerts
|

Universidades y Google News: visibilidad internacional a través de los medios de comunicación online

Abstract: Cómo citar este artículo/Citation: Herrero-Solana, V.; Arboledas, L.; Legerén-Álvarez, E. (2014 Resumen: La difusión de la actividad científica y la mediatización de la ciencia en la actualidad convergen en Internet. Ambos procesos contribuyen a la creación de la reputación online de las instituciones académicas. Este estudio discute si la capacidad investigadora de una universidad repercute en su presencia en los medios digitales. Para responder a esta cuestión se mide y compara la producción científica y las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 8 publications
1
1
0
5
Order By: Relevance
“…Universities presence was significantly higher in regional and local newspapers (70.25%), in line with previous studies (Barroso Osuna, 2000, Kim et al, 2007, Herrero-Solana et al, 2014Repiso et al, 2016).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Universities presence was significantly higher in regional and local newspapers (70.25%), in line with previous studies (Barroso Osuna, 2000, Kim et al, 2007, Herrero-Solana et al, 2014Repiso et al, 2016).…”
Section: Resultssupporting
confidence: 92%
“…Through content analysis and a citizen's survey, they were able to determined that greater exposure to these types of articles was related to low levels of reputation, lack of confidence and support to universities. Herrero-Solana et al (2014) studied if a scientific production of a university impacts their presence in digital media, comparing bibliometric indicators with the number of institutional news items recovered from Google News, regarding nine Spanish Universities. They concluded that, effectively, that those universities with higher bibliometric indicators also reach greater media exposure.…”
mentioning
confidence: 99%
“…La presencia de las universidades fue significativamente mayor en los periódicos de alcance regional y local (70,25%), en línea con estudios anteriores (Barroso Osuna, 2000; Kim et al, 2007;Herrero-Solana et al, 2014;Repiso et al, 2016).…”
Section: Resultsunclassified
“…Por lo que se reere al estado de la cuestión, no son muchos los trabajos existentes en España acerca de la relación entre universidad y prensa. Entre los pioneros está la tesis de Gloria Pérez Serrano (1984) sobre la presencia de la Universidad Nacional de Educación a Distancia (UNED) en prensa local, a los que siguieron las investigaciones de Barroso Osuna (2000), García Rivas (2003, Martel Escobar y Hernández Guerra (2004), Hernández Guerra y Martel Escobar (2006), Nieto Báez y Aguaded Gómez (2010), Nieto Báez (2014), Palencia-Leer Ors (2012), Legerén (2014) y Herrero-Solana et al (2014, entre otros.…”
Section: Introductionunclassified